Convergence of Police and Military Praxis: Pre-9/11 Training Diffusion in Post-9/11 Law Enforcement - Parker, Richard K (2019)
The terrorist attacks on September 11, 2001, changed law enforcement policy and practice forever. At a glance, one could argue that this was the seminal moment in U.S. law enforcement history where traditional police officer training and equipment quickly transitioned to training and equipment that some argue is more conducive to soldiers on a battlefield. Closer analysis of the changes in police training and equipment reveals that years earlier, the executive branch of the U.S. government initiated the transfer of military equipment to local, state, and federal law enforcement agencies to provide such resources in an effort to stem what has been known as the “war on drugs.” Thereafter, a number of legislative actions both prior to and since 9/11 appear to have contributed to the militarization of police in the United States. Add to these changes the phenomenon of active shooters and mass casualty incidents, and police officers are now facing previously unforeseen responsibilities and threats to their safety. They have responded by facilitating relationships with military and medical professionals to find solutions to ever-shifting challenges. Much of the literature holds that police armed with nontraditional weapons and training contribute to a sociological and governmental state-controlled force dynamic which favors those in power and threatens minority classes. Broadly speaking, the literature has focused its attention on citizen perceptions of police equipment and training. The purpose of this study was to determine police officer perceptions of the militarization of police and, more broadly, gain their insight into its place in law enforcement operations. A phenomenological qualitative approach using interviews of on-duty police officers representing three different law enforcement agencies was undertaken in an effort to capture differences and similarities in their perceptions of the militarization phenomenon and their approaches to training and equipment when addressing new and emerging threats